Multi-emissivity setting in thermal imaging based on visible-light image segmentation - Ding De-hong; Fang Kui; Yu He-xiang; Qian Ke-jun; Chen Yi-neng; Cui Dai-jun (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Emissivity is an accuracy influencing factor during infrared temperature measurement which focusing on regular geometry in laboratory under the condition of single emissivity. But in practical application, the target is often irregular with multi-emissivity,, and if following "idealized" method in laboratory, it will lead to inevitable error. This paper presents a method for a complex target object with the collection of multiple emissivities in infrared image after measurement. Both visible and infrared images were collected in the same field of view at the same time using binocular video to segment target regionally through visible image. The emission rate in corresponding region was set based on regional growing algorithm. Heat conduction equation was used as a reference to smooth the boundary area. After testing image evaluation parameters accordingly, results obtained via this infrared temperature measurement method are closer to the true value and precise compared with conventional ones judged from objective measurements. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3913